2021
DOI: 10.1080/21870764.2021.1939241
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetic CuFe2O4/Fe2O3 core-shell materials and their application in photo-Fenton-like process with oxalic acid as a radical-producing source

Abstract: Le (2021): Synthesis of magnetic CuFe 2 O 4 /Fe 2 O 3 core-shell materials and their application in photo-Fenton-like process with oxalic acid as a radical-producing source, Journal of Asian Ceramic Societies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, table 1 also compares their BET specific surface area, which reveals the role of the synthesis method, especially the influences of heating process on the surface area. In our previous studies, the ferrite materials prepared by annealing at high temperatures often showed restricted surface area (14.33 m 2 g -1 [15] or 1.159 m 2 g -1 [23] ). Interestingly, all three ferrite samples of this work show impressively high specific surface area, varying from 127.72 to 188.04 m 2 g -1 , indicating that the coprecipitation without annealing is appropriate for the synthesis of ferrite adsorbents.…”
Section: Characterization Of Metal Ferritesmentioning
confidence: 99%
“…Moreover, table 1 also compares their BET specific surface area, which reveals the role of the synthesis method, especially the influences of heating process on the surface area. In our previous studies, the ferrite materials prepared by annealing at high temperatures often showed restricted surface area (14.33 m 2 g -1 [15] or 1.159 m 2 g -1 [23] ). Interestingly, all three ferrite samples of this work show impressively high specific surface area, varying from 127.72 to 188.04 m 2 g -1 , indicating that the coprecipitation without annealing is appropriate for the synthesis of ferrite adsorbents.…”
Section: Characterization Of Metal Ferritesmentioning
confidence: 99%
“…This composite was created using a modified chemical process, commonly known as the bottom-up approach in nanotechnology, according to references (Massoud-Sharifi et al, 2019), (Tran Thi et al, 2021). The precursors of the CdS nanocomposite were cadmium chloride hydrate (CdCl 2 .2H 2 O) and thiourea.…”
Section: Magnetic Nanoparticles Of Cufe 2 O 4 Cuo and Cds Immobilize...mentioning
confidence: 99%